Análisis, diseño e implementación de un sistema de control administrativo del personal de la unidad educativa Pulgarcito Americano Elga, mediante la técnica biométrica de la huella dactilar, utilizando lenguaje de programación open source, metodología de desarrollo conducido por características, y gestor de base de datos postgres. - Pástor Toala, Xavier Andrés (2015)
Education Unit "Pulgarcito Americano Elga" owned by the Reyes family Loayza, located in the province of El Oro in the city of Machala, had several problems for the control and payment of staff of the Academic Unit. With the above urgently how to analyze, design and implement a system of administrative control staff of the Education Unit ""Pulgarcito Americano Elga" was noted.